Seasonal pattern of hepatitis E virus prevalence in swine in two different geographical areas of China - LU, Y. H. (Cambridge University Press, 2013)
We studied seasonal patterns of swine hepatitis E virus (HEV) infection in China. From 2008 to 2011, 4200 swine bile specimens were collected for the detection of HEV RNA. A total of 92/2400 (3·83%) specimens in eastern China and 47/1800 (2·61%) specimens in southwestern China were positive for HEV. Seasonal patterns differing by geographical area were suggested. In eastern China, the major peak of HEV RNA prevalence was during March–April, with a minor peak during September–October, and a dip during July–August. In southwestern China, the peak was during September–October and the dip during March–April. The majority of subtype 4a cases (63/82, 76·83%) were detected in the first half of the year, while the majority of subtype 4b cases (26/29, 89·66%) were concentrated in the second half of the year, suggesting that different subtypes contribute to different peaks. Our results indicate that the distribution of HEV subtypes is associated with seasonal patterns.